Povzetki in ekskurzije 3. slovenski geološki kongres, Bovec, september 2010 - Zupan Hajna, Nadja; Horvat, Aleksander; Košir, Adrijan; Otoničar, Bojan (ZRC SAZU, Založba ZRC, 2010)
geology;proceedings;Slovenia;geologija;posvetovanja;Slovenija